Development of auditory brainstem signal acqusition system - Rubita Sudirman, author; Mastura Shafinaz Zainal Abidin, author; Nurhanim Abu Sama, author; International Conference on Control, Instrumentation & Mechatronic Engineering (2nd: 2009: Melaka) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL